Decision Support System for Online Learning Media Selection During the Pandemic Period - Fitriyani Fitriyani; Yuyi Andrika; Melati Suci Mayasari; Anisah Anisah (SISFOTENIKA, 2021)
Online learning media is one of the uses of technology in the form of software. During the COVID-19 pandemic, the government issued a policy for distance learning, so to facilitate the teaching and learning process between teachers and students who are in different places, online learning media are needed that can be used by educators or students. For this reason, researchers conducted research on online learning media. Alternatives used by researchers include google classroom, zoom free, google meeting free, and WhatsApp group. The criteria used by the researcher are easy to access, according to purpose, time limit for access, interactivity. The method used is the SAW (Simple Additive Weighting) method. This method is a method for calculating the weights of the criteria and alternatives so that the final weight of each alternative is obtained so that it is known which alternative has the highest value weight that can be recommended to decision makers. From the research results obtained WhatsApp group with a weight of 0.75, google classroom with a weight of 0.74, google meeting free with a weight of 0.67, zoom free with a weight of 0.55. It is necessary to do further research using different methods or combining several methods so that the research conducted by this researcher is not the end of research with the same discussion.